The Effect Of Training, Leadership And Achievement Motivation On The Self-Confidence Of Members Of The Tiger Bengkulu Taekwondo Club - Sari, Dwi Mafika; Anggriani, Ida; Putra, Iswidana Utama (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the effect of training, leadership and motivation to achieve on the self-confidence of members of The Tiger Bengkulu Taekwondo, both partially and simultaneously. The analysis methods used were validity testing, reliability testing, multiple linear regression, coefficient of determination, F-test, and t-test. Data collection was conducted using questionnaires. The sample in this study consisted of 73 members of Taekwondo The Tiger BengkuluTraining partially had a significant effect on the self-confidence of members of Taekwondo The Tiger Bengkulu because the significance value was 0.000 < 0.05. Leadership partially had a significant effect on the self-confidence of members of Taekwondo The Tiger Bengkulu because the significance value was 0.002 < 0.05. Achievement motivation partially had a significant effect on the self-confidence of members of Taekwondo The Tiger Bengkulu because the significance value was 0.000 < 0.05. Training, leadership, and achievement motivation simultaneously had a significant effect on the self-confidence of members of Taekwondo The Tiger Bengkulu because the significance value was 0.000 < 0.05.